2007
DOI: 10.1007/s11771-007-0102-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of mibolerone

Abstract: Abstract:A simple and effective route for the synthesis of mibolerone was described starting from the estr-5(10)-en-3,17-dione in four steps with the overall yield of 47.0 %. Thus, two methods for key intermediate methylnorandrost were investigated: one(method A) starting from estr-4-en-3,17-dione underwent 3-keto group protected with ethyl orthoformate to give 3-ethoxy-3,5-dien-estr-17-one, the other(method B) from estr-5(10)-en-3,17-dione and protected 3-keto group to give 3,3-dimethoxy-estr-5(10)-7-one in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It was reported that platinum-based concurrent chemoradiotherapy had been accepted by the National Comprehensive Cancer Network as the standard recommendation for locally advanced NPC since the Intergroup 0099 study was published in 1998 [7]. And its superiority in clinical performance over traditional radiotherapy had been demonstrated in subsequent RCT studies [8] and MAs [9, 10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that platinum-based concurrent chemoradiotherapy had been accepted by the National Comprehensive Cancer Network as the standard recommendation for locally advanced NPC since the Intergroup 0099 study was published in 1998 [7]. And its superiority in clinical performance over traditional radiotherapy had been demonstrated in subsequent RCT studies [8] and MAs [9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…As the SUCRA results revealed, therapeutic strategies based on concurrent chemoradiotherapy, including concurrent chemoradiotherapy alone or combined with adjuvant or neoadjuvant chemotherapy, were recommended as the first-line therapies, when the characteristics of individuals are not clarified. It was reported that platinum-based concurrent chemoradiotherapy had been accepted by the National Comprehensive Cancer Network as the standard recommendation for locally advanced NPC since the Intergroup 0099 study was published in 1998 [ 7 ]. And its superiority in clinical performance over traditional radiotherapy had been demonstrated in subsequent RCT studies [ 8 ] and MAs [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in addition to the participant threshold to be satisfied, a transaction can be successful only if r (< t − 1) privileged participants agree the transaction. In the following, we investigate the joint Bitcoin trading in this scenario and present a variant to cater for the privileged participants included in the threshold (Ghodosi et al 2012;Tang 2007). We first describe the "key generation" procedure.…”
Section: System Parametersmentioning
confidence: 99%
“…It is easy to see that the resulting signature can be unblinded (Tang 2007). In this way, we provide a partially blind multi-signature based-approach so that some privileged participants must be included into the threshold.…”
Section: The Dealer Randomly Chooses Integersmentioning
confidence: 99%
“…[10,11] The intrinsic properties of C/C composites, including the fiber architecture, matrix microstructure, and bulk density, are closely concerned with the ablation property of the composites. [12][13][14] Carbon fibers and various kinds of carbon matrices (pitch carbon, resin carbon, and pyrolytic carbon [PyC]) exhibit different ablation properties considering their different microstructures. C/C composites with a high graphitization degree and density usually possess better ablation resistance due to the reduced reactive sites and diffusion paths for oxidation gases.…”
Section: Introductionmentioning
confidence: 99%